PROGRAM SEKOLAH PARENTING UNTUK MENINGKATKAN POLA ASUH ORANG TUA TERHADAP ANAK DALAM PERSPEKTIF PENDIDIKAN ISLAM DI PRIM KLANG LAMA MALAYSIA - Rachmawati, Dian Karina; Insani Wahyu Mubarok (Universitas Muhammadiyah Surabaya, 2024)
This research was conducted at SB. Aisyiyah Kampung Pandan Malaysia aimed to provide counseling in the form of parenting to parents. Several problems must be addressed, such as some parents working as migrant workers and entrepreneurs. During their busy schedule, they are expected to have time to teach about several characteristics, namely, a sense of love for the country and forming religiosity in children through daily habituation. Parenting studies for parents are expected to be carried out regularly to produce superior generations in SB. Aisyiyah Kampung Pandan Malaysia. Parents and students attended this activity. The method used was observation in the form of interviews with parents and data on students aged 3 to 8 years. The target output that wants to be produced from community service is parenting activities for parents of student guardians at SB. Aisyiyah Kampung Pandan Malaysia and in the form of scientific articles on community services.